Ultrastructure of rat sciatic nerve at the streptozotocin-induced neuropathy conditions under administration of alpha-lipoic acid preparations. - Dronov, S. M. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Diabetic polyneuropathy is one of the most common long-term complications of diabetes. Hyperglycemias caused by ischemia and peroxidation of lipids are the presumed cause of diabetic neuropathy. Appointment of alpha-lipoic acid can restore the function of peripheral nerves, preventing the development of autonomic and trophic disorders. Objective. To determine the extent of changes in the ultrastructure of the sciatic nerve in rats with streptozotocin-induced simulated peripheral neuropathy in experimental therapy with α-lipoic acid. Methods. The research was conducted on 22 white rats divided randomly in 3 groups: group 1 – intact animals; group 2 – rats with streptozotocin-induced neuropathy; group 3 – rats with streptozotocin neuropathy + alpha-lipoic acid. Diabetes mellitus was induced in rats by a single intraperitoneal injection of streptozotocin (50 mg/kg). alpha-lipoic acid was administered intraperitoneally and intragastrically once per day during 40 days from the 56th day after streptozotocin injection. Transmission electron microscopy was performed on the 40th day of alpha-lipoic acid administration. Results. Administration of alpha-lipoic acid activates compensatory-adaptive processes in neuronal cells, reduces the severity of violations in the composition of myelinated nerve fibers, contributes to a distinct axonal spruting, causes the reduction of asymmetrically distributed electron density in the lamellar structure of myelin, indicating an increase in the insulation of axons of the sciatic nerve fibers of rats. Conclusion. Experimental studies confirm high neuroprotective potential of alpha-lipoic acid in streptozotocin-induced neuropathy.